2013
DOI: 10.1088/1748-3182/8/4/046008
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between wingbeat frequency and resonant frequency of the wing in insects

Abstract: In this study, we experimentally studied the relationship between wingbeat frequency and resonant frequency of 30 individuals of eight insect species from five orders: Odonata (Sympetrum flaveolum), Lepidoptera (Pieris rapae, Plusia gamma and Ochlodes), Hymenoptera (Xylocopa pubescens and Bombus rupestric), Hemiptera (Tibicen linnei) and Coleoptera (Allomyrina dichotoma). The wingbeat frequency of free-flying insects was measured using a high-speed camera while the natural frequency was determined using a lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…Until these alternatives are explored further, we suggest that the simplest interpretation of our data is support for the stiff element hypothesis. This conclusion is in general agreement with the conclusion of Ha et al (2013), that the fundamental frequency of the wings is significantly different from the wingbeat frequency. Ha et al (2013) found fundamental frequency (lowest mode) exceeded wingbeat frequency for all insect groups tested except Hymenopterans, while we found the lowest mode exceeded wingbeat frequency for A. mellifera (Hymenoptera).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Until these alternatives are explored further, we suggest that the simplest interpretation of our data is support for the stiff element hypothesis. This conclusion is in general agreement with the conclusion of Ha et al (2013), that the fundamental frequency of the wings is significantly different from the wingbeat frequency. Ha et al (2013) found fundamental frequency (lowest mode) exceeded wingbeat frequency for all insect groups tested except Hymenopterans, while we found the lowest mode exceeded wingbeat frequency for A. mellifera (Hymenoptera).…”
Section: Resultssupporting
confidence: 92%
“…This conclusion is in general agreement with the conclusion of Ha et al (2013), that the fundamental frequency of the wings is significantly different from the wingbeat frequency. Ha et al (2013) found fundamental frequency (lowest mode) exceeded wingbeat frequency for all insect groups tested except Hymenopterans, while we found the lowest mode exceeded wingbeat frequency for A. mellifera (Hymenoptera). Ha et al (2013) measured the first longitudinal mode for the wings of several species of insect, but on excised wings, which are stiffer than in vivo wings (Mengesha et al, 2011).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations